Exploring Children's Morality: Theory, Data, and Practice in Early Childhood Education Yogyakarta - Rosyida, Fatia; Syamsudin, Amir; Yusuf, Lisanun Thoyyibah (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2025)
The moral development of early childhood is crucial for shaping their character and social interaction. This study examines the efficacy of the Project Approach in fostering moral development in young children within early childhood education settings.  The study employed a mixed-methods approach, combining quantitative scoring of moral development with qualitative analysis of the children's responses. Using a five-point scoring rubric, the researchers assessed the moral reasoning abilities of the child participants through observations. The findings indicate that a majority of the children exhibit notable progress in their moral development, predominantly clustering within the "Developing" category, suggesting a shift towards more nuanced moral reasoning. The Project Approach's emphasis on real-world social interaction, critical thinking, and empathy cultivation appears to positively influence children's moral development. The results also highlight the importance of educational approaches that prioritize the cultivation of both cognitive and emotional aspects of morality. The study's conclusion is that the Project Approach significantly supports the development of more mature moral principles in students, facilitating children's transition to higher stages of moral development and fostering the foundations of healthy and sustainable morality. This result contributed to a more comprehensive understanding of how best to support children's moral growth.